ARTHUR SCHOPENHAUER'S QUEST OF MUSICAL REPERTORY, ARHYTHMIA AND WILLINGNESS - Wika Dwi Darma; Jonathan Jonathan; Frenky Albert Timotius; Jasmine Ambun Sintalegawa; Aprianto Wirawan (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2023)
The purpose of this research paper is to explore the extent of Arthur Schopenhauer's thoughts in seeing and penetrating ideas, desires, preferences, and plausibility through distancing, colliding, and giving meaning when he encounters music, social issues, and multi-disciplines without losing the self-image of music. Qualitative research with data search on previous writings through journals as a secondary source became a room to argue Arthur Schopenhauer's thoughts with intelligence, non-simplification of something complex and enjoy without the need for validation. Results show that the objectivation of the will as Arthur Schopenhauer's central idea leads to visual space in the frame of images, songs, lyrics, narratives, processes, and struggles as the essence of music that permeates and boils down to reflection and asceticism.